A Theoretical Study on the Traditional Concrete Mix Design Method (International Journal of Communication Systems and Network Technologies, 2020)
Concrete, as a fundamental building material, has undergone numerous advancements, yet the traditional concrete mix design methods remain at the core of construction practices. This journal paper presents a theoretical study aimed at reevaluating and enhancing our understanding of the traditional concrete mix design approach. Through an extensive review of historical perspectives, current practices, and emerging research, this study seeks to shed light on the theoretical underpinnings that govern the formulation of concrete mixes. The findings from this theoretical exploration aim to contribute to the ongoing discourse on concrete technology, providing a theoretical framework for practitioners, researchers, and educators in the field. The theoretical insights derived from this study could potentially guide the evolution of concrete mix design methods, offering a foundation for the development of more robust, sustainable, and context-sensitive concrete formulations.
Keywords: Concrete Mix Design; Traditional Methods; Theoretical Study; ACI; British Method; Sustainability